2012
DOI: 10.1259/bjr/53282892
|View full text |Cite
|
Sign up to set email alerts
|

Breast tomosynthesis and digital mammography: a comparison of diagnostic accuracy

Abstract: The diagnostic accuracy of BT was superior to DM in an enriched population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 43 publications
5
97
0
4
Order By: Relevance
“…Typically, cancerous tumor has high density compared to surrounding region and can be easily distinguished from other regions. Studies [5][6][7] show that it gives a sensitivity of 68% to 88% (or as low as 48% for extremely dense breasts) and specificities ranging from 82% to 98%. In addition, it has the following disadvantages:…”
Section: Comparison With Mammographymentioning
confidence: 99%
“…Typically, cancerous tumor has high density compared to surrounding region and can be easily distinguished from other regions. Studies [5][6][7] show that it gives a sensitivity of 68% to 88% (or as low as 48% for extremely dense breasts) and specificities ranging from 82% to 98%. In addition, it has the following disadvantages:…”
Section: Comparison With Mammographymentioning
confidence: 99%
“…148,149 Studies have reported 7.2% -53% increase in cancer detection and 20% -59% reduction in recall rates with supplemental DBT. 31,44,45,150,151 Importantly, radiation dose to the dense tissue is lower for DBT than digital mammography (DM) for dense breasts; 43 therefore DBT is preferable to DM in terms of performance and dose, albeit it appears women with fatty breasts get higher dose on DBT. 152 Another approach suitable for imaging the dense breast is molecular breast imaging (MBI) or BreastSpecific Gamma Imaging (BSGI).…”
Section: Imaging the Dense Breastmentioning
confidence: 99%
“…The readers had experience of DBT reading from previous studies [21][22][23]. Two blinded readers evaluated the DBT reading sequence independently from the two blinded readers of the DM reading sequence.…”
Section: Study Population and Image Readingmentioning
confidence: 99%